Prevalence Of Pelvic Floor Dysfunction Among Postpartum Women - A Cross Sectional Study - Harshinee N, Harshinee N; Meena, T. S. (Journal of Neonatal Surgery, 2025)
Background: Pelvic floor dysfunction (PFD) significantly affects women after childbirth, often overlooked despite its effects on daily life, emotions, and relationships. In India, postpartum care rarely includes routine checks for this condition, leaving many cases unnoticed. Objective: This study set out to measure how common PFD is among women after giving birth and pinpoint the factors that increase its likelihood, focusing on a hospital in Chennai. Methods: We surveyed 165 women who were 6 to 12 weeks postpartum at Sree Balaji Medical College and Hospital in Chennai, between March and May 2025. They filled out two questionnaires—the PFDI-20 to check for PFD symptoms and the PFIQ-7 to see how it affected the quality of their lives. We also gathered details about their age, delivery experience and habits, then looked for patterns using statistical tests, considering results meaningful if p value was less than 0.05. Results: About 45% of the women (74 out of 165) had some form of PFD. The most frequent problem was urinary distress (58%, or 96 women), followed by pelvic organ prolapse (44%, or 72 women) and bowel issues (37%, or 61 women). On average, their PFDI-20 score was 18.5 (with a spread of ±6.5), and their PFIQ-7 score was 13.8 (±5.2), showing a noticeable impact on their well-being. Interventions like using forceps or vacuum during delivery (p = 0.001), a long second stage of labor (p = 0.013), perineal tear (p = 0.003), being over 30 years old (p = 0.05), and not doing Kegel exercises (p < 0.001) were strongly tied to PFD. Having multiple births (p = 0.057) or a baby weighing 3.5 kg or more (p = 0.052) also seemed to play a role, though the link was less certain. Conclusion: Nearly half the women in this study dealt with PFD after childbirth, with urinary distress being the biggest concern. Early screening and pelvic floor exercises are essential for prevention.